Alasdair MacIntyre, utopianism and the politics of social institutions - Burns, Tony (Taylor & Francis, 2018)
In what follows I shall consider what Alasdair MacIntyre has to say about utopianism, from the standpoint of someone who has an interest in the kind of politics that takes place within social institutions. The discussion has two parts. In the first part I survey the various comments that MacIntyre has made about utopianism in his writings over the years, from the publication of After Virtue in 1981 down to the present. In the second part I discuss the relevance of these ideas for those seeking to develop a critique of the uses and abuses of power within contemporary social institutions.